استراتيجيات تعلم المفردات العربية لدى طالبات المستوى الثاني من قسم الإعداد بجامعة الراية والاستفادة منها لارتقاء المستوى اللغوي - Raudaturrohmah (Rayah Al-Islam, 2018)
The study aimed at learning Arabic vocabulary strategies for second-semester students from the Preparatory Department at STIBA Ar-Raayah and making use of them to improve the linguistic level. The study used an analytical descriptive method to describe the strategies of learning the Arabic vocabulary used by a sample of second semester students from the Preparatory Department at STIBA Ar-Raayah. The resairch was conducted in the field to collect, organize and analyze the real information. The results of this study were: The strategies of learning the Arabic vocabulary used by the sample were study divided into five they are: the strategy of concluding the meaning from the context, the strategy of taking notes, the strategy of cooperative learning, and the strategy of using representation. The strategies improve the student’s as follow: when students use a strategy to derive meaning from the context, they develop their memories of grammatical and grammatical rules and their functions, when the strategy of taking notes uses the development of written skill, When they use a collaborative learning strategy, the skill of speech increases, when they use the representation strategy to remember the vocabulary they have learned, and the use of dictionaries increases information about new vocabulary.